2010
DOI: 10.1074/jbc.m110.128801
|View full text |Cite
|
Sign up to set email alerts
|

In Silico Docking and Electrophysiological Characterization of Lacosamide Binding Sites on Collapsin Response Mediator Protein-2 Identifies a Pocket Important in Modulating Sodium Channel Slow Inactivation

Abstract: The anti-epileptic drug (R)-lacosamide ((2R)-2-(acetylamino)-N-benzyl-3-methoxypropanamide (LCM)) modulates voltage-gated sodium channels (VGSCs) by preferentially interacting with slow inactivated sodium channels, but the observation that LCM binds to collapsin response mediator protein 2 (CRMP-2) suggests additional mechanisms of action for LCM. We postulated that CRMP-2 levels affects the actions of LCM on VGSCs. CRMP-2 labeling by LCM analogs was competitively displaced by excess LCM in rat brain lysates. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
84
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 71 publications
(93 citation statements)
references
References 53 publications
7
84
2
Order By: Relevance
“…It has been reported that CRMP2 is involved in kinesin-1-dependent transport of the Sra1-WAVE1 complex (Arimura et al, 2009) and in regulation of trafficking by linking endocytic regulatory proteins to dynein motors (Rahajeng et al, 2010). CRMP2 has been reported to be able to directly bind to voltage-dependent Na + channels, modulating the channel's slow inactivation (Dustrude et al, 2013;Wang et al, 2010). CRMP2 also modulates Na v 1.7 trafficking via SUMOylation (Dustrude et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that CRMP2 is involved in kinesin-1-dependent transport of the Sra1-WAVE1 complex (Arimura et al, 2009) and in regulation of trafficking by linking endocytic regulatory proteins to dynein motors (Rahajeng et al, 2010). CRMP2 has been reported to be able to directly bind to voltage-dependent Na + channels, modulating the channel's slow inactivation (Dustrude et al, 2013;Wang et al, 2010). CRMP2 also modulates Na v 1.7 trafficking via SUMOylation (Dustrude et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Catecholamine A-differentiated (CAD) Cell Culture-CAD cells were cultured exactly as described (20,21).…”
Section: Methodsmentioning
confidence: 99%
“…All mutations were made as previously described using Quikchange II XL (Agilent Technologies, Santa Clara, CA) and verified by DNA sequencing [30]. Constructs for wildtype and dominant negative CdK5 were purchased from Addgene (Cambridge, MA).…”
Section: Generation Of Crmp-2 Dsred and Crmp-2 Mutantsmentioning
confidence: 99%
“…The neuronally derived CAD cells were grown at 37°C and in 5% CO 2 as previously described [30,31]. CAD cells were transfected as described above.…”
Section: Culturing Catecholamine a Differentiated (Cad) Cellsmentioning
confidence: 99%